A Company Profile: A Way to Get More Customers for Irama Mas Yamaha Music School Surabaya - Pamela Felita Santoso; Julia Eka Rini (Kata Kita: Journal of Language, Literature, and Teaching, 2015)
The absence of the Company Profile at Irama Mas Yamaha Music School (IMYMS) is a problem that can lead to several problems in convincing and attracting customers about its credibility and its uniqueness. Most customers only know that Irama Mas is a Yamaha Music School, while actually, it is more than just a music school. As a music company, Irama Mas needs to have more customers to support its successful in a business world. Therefore, the bilingual company profile with some chosen features is made to help IMYMS clearly explain and attract customers about its products and services and market IMYMS. This company profile can also be used as a guidance in making its website since it does not have a website.